2018
DOI: 10.1080/14786419.2018.1511553
|View full text |Cite
|
Sign up to set email alerts
|

A new phenolic glycoside from the Idesia polycarpa Maxim. leaves

Abstract: Phytochemical investigation on the ethyl acetate extract of Idesia polycarpa Maxim. leaves led to the isolation of four phenolic glycoside isomers (1-4). Compound 2 appeared to be new reported phenolic glycoside, while compound 1 was the first time isolated from the titled species. Their structures were established by IR, UV, HRESI-MS and 1D and 2D NMR spectroscopies analysis and comparison of spectral data with previously reported data. The compounds 3 and 4 showed stronger activity of scavenging the DPPH fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Interestingly, we found that EF-D mainly contained 1-[(4′-O-(Z)-p-coumaroyl)- β -D-glucopyranosyl]-oxy-2-phenol and 1-[(4′-O-(E)-p-coumaroyl)- β -D-glucopyranosyl]-oxy-2-phenol [ 35 ] ( Figure 7 ). We identified the two compounds by comparing to the standard substances which were isolated from the defatted fruit of I. polycarpa and identified by mass spectrometry in our laboratory [ 36 ]. The antioxidant activities and cell cytotoxicity of two new monomers have been proven [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, we found that EF-D mainly contained 1-[(4′-O-(Z)-p-coumaroyl)- β -D-glucopyranosyl]-oxy-2-phenol and 1-[(4′-O-(E)-p-coumaroyl)- β -D-glucopyranosyl]-oxy-2-phenol [ 35 ] ( Figure 7 ). We identified the two compounds by comparing to the standard substances which were isolated from the defatted fruit of I. polycarpa and identified by mass spectrometry in our laboratory [ 36 ]. The antioxidant activities and cell cytotoxicity of two new monomers have been proven [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…We identified the two compounds by comparing to the standard substances which were isolated from the defatted fruit of I. polycarpa and identified by mass spectrometry in our laboratory [ 36 ]. The antioxidant activities and cell cytotoxicity of two new monomers have been proven [ 36 ]. Our findings are consistent with the previous studies and demonstrate that the defatted fruit of I. polycarpa acts as a natural product for ameliorating NAFLD.…”
Section: Discussionmentioning
confidence: 99%